FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN TEKNOLOGI - Nila Sapit Tri; Fauziati, Popi; Mukhlizul Hamdi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to examine the influence of managerial ownership, institutional ownership, growth opportunity, profitability, and leverage on accounting conservatism. The population in this research consists of 47 technology companies listed on the Indonesia Stock Exchange, with a purposive sampling method resulting in 18 companies as the research sample. The observation period is 3 years, from 2020 to 2022, with a total of 54 samples. This study uses multiple linear regression analysis with the help of SPSS version 29. The research results show that profitability has a positive effect on accounting conservatism. The variables of managerial ownership, institutional ownership, growth opportunity, and leverage do not have an effect on accounting conservatism.